Proteomic analyses unraveling water stress response in two Eucalyptus species originating from contrasting environments for aridity - Martins, Rayana de Sá; Faria, José Marcio Rocha; Rossini, Bruno César [UNESP]; Marino, Celso Luís [UNESP]; dos Santos, Lucilene Delazari [UNESP]; José, Anderson Cleiton (Springer Nature, 2020)
Eucalyptus are widely cultivated in several regions of the world due to their adaptability to different climatic conditions and amenable to tree breeding programs. With changes in environmental conditions pointing to an increase in aridity in many areas of the globe, the demand for genetic materials that adapt to this situation is required. Therefore, the aim of this work was to identify contrasting differences between two Eucalyptus species under water stress through the identification of differentially abundant proteins. For this, total protein extraction was proceeded from leaves of both species maintained at 40 and 80% of field capacity (FC). The 80% FC water regime was considered as the control and the 40% FC, severe water stress. The proteins were separated by 2-DE with subsequent identification of those differentially abundant by liquid nanocromatography coupled to high resolution MS (Q-Exactive). Comparative proteomics allowed to identify four proteins (ATP synthase gamma and alpha, glutamine synthetase and a vacuolar protein) that were more abundant in drought-tolerant species and simultaneously less abundant or unchanged in the drought- sensitive species, an uncharacterized protein found exclusively in plants under drought stress and also 10 proteins (plastid-lipid, ruBisCO activase, ruBisCO, protease ClpA, transketolase, isoflavone reductase, ferredoxin-NADP reductase, malate dehydrogenase, aminobutyrate transaminase and sedoheptulose-1-bisphosphatase) induced exclusively in the drought-tolerant species in response to water stress. These results suggest that such proteins may play a crucial role as potential markers of water stress tolerance through the identification of species-specific proteins, and future targets for genetic engineering.
Keywords: Eucalypts; Proteins; Proteome; Sensitive species; Tolerant species; Water stress